Complaint Handling Systems In The Public Sector: A Comparative Analysis Between Indonesia and Australia - Harijanti, Susi Dwi (Universitas Muhammadiyah Yogyakarta, 2020)
This article deals primarily with complaint handling system with reference to an ombudsman that established by the government as opposed to the private ombudsman variety in Indonesia and Australia’s jurisdictions. In practice, group of people or persons have often arisen complaints or grievances in public service, and it requires solutions. It is widely known that the Ombudsman office has long been regarded as an effective office in resolving people complaint. This is mainly because the nature of the Ombudsman as an independent and impartial institution. This article argues that regardless of the different context of introduction of an ombudsman in Indonesia and Australia because of different political and social context, however, the performance of ombudsman in both countries has showed significant role in enhancing public services through their expanded mandates and stronger powers.